Figurative language in song lyric “Take Me to Your Heart” by MLTR - Rahman, Abdul Ambar (Universitas Sarjanawiyata Tamansiswa, 2023)
The material object of this paper is one of the songs sung by a band from Denmark, namely, Michael Learns to Rock, entitled